Reliability of symmetry differences of dynamic variables during countermovement jump - Menzel, H. J.; de Andrade, A. P.; Bertú, F.; Araújo, S.; Chagas, M. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The aim of the study was the determination of the reliability of symmetry differences of peak force, impulse and peak power during Countermovement Jump on a double force platform. The subjects were 12 Brazilian female professional volleyball players who performed five CMJs on a double force platform. Symmetry differences of peak force, impulse and peak power were determined. In order to verify the reliability, the Intraclass Correlation Coefficient was calculated. While symmetry difference of peak force and impulse present an ICC > 0.90, symmetry difference of peak power has only an ICC of 0.77. It can be concluded that the determination of symmetry differences by peak force and impulse during CMJ on a double force platform have higher reliability than symmetry differences of peak power.